Breast Cancer Treatment Delay in SafetyNet Health Systems, Houston Versus Southeast Brazil. (28th March 2022) - Shafaee, Maryam Nemati; Silva, Leonardo Roberto; Ramalho, Susana; Doria, Maira Teixeira; De Andrade Natal, Rodrigo; Cabello, Victor; Cons, Livia; Pavanello, Marina; Zeferino, Luiz Carlos; Mano, Max S; Linck, Rudinei Diogo Marques; Batista, Leticia Souza; et al.
Abstract : This article examines the impact of treatment delay on the outcomes of patients with breast cancer, comparing results of those utilizing the public health systems in Harris County (Texas, USA) and Southeast Brazil. Abstract: Background: Breast cancer outcomes among patients who use safety-net hospitals in the highly populated Harris County, Texas and Southeast Brazil are poor. It is unknown whether treatment delay contributes to these outcomes. Methods: We conducted a retrospective cohort analysis of patients with non-metastatic breast cancer diagnosed between January 1, 2009 and December 31, 2011 at Harris Health Texas and Unicamp's Women's Hospital, Barretos Hospital, and Brazilian National Institute of Cancer, Brazil. We used Cox proportional hazards regression to evaluate association of time to treatment and risk of recurrence (ROR) or death. Results: One thousand one hundred ninety-one patients were included. Women in Brazil were more frequently diagnosed with stage III disease (32.3% vs. 21.1% Texas; P = .002). Majority of patients in both populations had symptom-detected disease (63% in Brazil vs. 59% in Texas). Recurrence within 5 years from diagnosis was similar 21% versus 23%. Median time from diagnosis to first treatment defined as either systemic therapy (chemotherapy or endocrine therapy) or surgery, were comparable, 9.9 weeks versus 9.4 weeks. Treatment delay was not associated with increased ROR or death. Higher stage at diagnosis was associated with both increased ROR and death. Conclusion: Time from symptoms to treatment was considerably long in both populations. Treatment delay did not affect outcomes. Impact: Access to timely screening and diagnosis of breast cancer are priorities in these populations. Abstract : This article examines the impact of treatment delay on the outcomes of patients with breast cancer, comparing results of those utilizing the public health systems in Harris County (Texas, USA) and Southeast Brazil.